Cholelithiasis and its Relationship with Serum Lipids in a Tertiary Care Hospital of Rajshahi (Sir Salimullah Medical College Journal, 2022)
Background: Gallstone disease (GD) is one of the most prevalent gastrointestinal disease in worldwide and also in Bangladesh. High triglyceride and low HDL (high density lipoprotein) are associated with cholelithiasis whereas total cholesterol and LDL (low density lipoprotein) have less association.Objectives: To find out the association of cholelithiasis and lipid profile.Material and Methods: This case-control study was conducted on 300 patients in the department of surgery, Rajshahi Medical College Hospital from September, 2018 to August, 2019. Participants were divided into two groups; group A (case group- 150 patients) and group B (control group-150 patients). After overnight fasting 5 ml venous blood was collected and serum lipid profile was measured. Outcomes were expressed in the form of figures and tables.Result: The mean age in case group were 39.79±8.16 years and in control group 38.67±7.99 years respectively with female predominance (72%) and male to female ratio was 1:2.57. out of 150 participants in case group 61% (91) had cholesterol stone. TG level was high both in cholesterol stone 57 (62.62%) and mixed stone 35 (59.32%) in case group. The mean BMI (25.73±2.10) in case group were significantly higher. Post-operative histopathology shown 2 (1.33%) patients associated with malignancy.Conclusion: The increased lipid profile can be good indicator for gall stone diseases and female are more susceptible to form gallstone who have high cholesterol level. Obesity is a risk factor for gallstone so people should maintain an ideal body weight. Gallstones are predisposing factor for malignancy.Sir Salimullah Med Coll J 2021; 29(2): 95-99